1988
DOI: 10.1128/jb.170.3.1143-1147.1988
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate transport and arsenate resistance in the cyanobacterium Anabaena variabilis

Abstract: Cells of the cyanobacterium Anabaena variabiis starved for phosphate for 3 days took up phosphate at about 100 times the rate of unstarved cells. Kinetic data suggested that a new transport system had been induced by starvation for phosphate. The inducible phosphate transport system was quickly repressed by addition of Pi.Phosphate-starved cells were more sensitive to the toxic effects of arsenate than were unstarved cells, but phosphate could alleviate some of the toxicity. Arsenate was a noncompetitive inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
2
4

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 26 publications
0
42
2
4
Order By: Relevance
“…However, elevated levels of Pi increased the uptake rate of phosphorus (p , 0.05) (Fig. 4B), which is inconsistent with the report of Thiel (1988), who found that cyanobacteria showed higher rates of phosphate uptake under phosphate-limited conditions. Previous data had indicated that Cylindrospermopsis raciborskii was opportunistic with respect to Pi (Istvá novics et al 2000) and had rapid DIC uptake and storage capacity (Posselt et al 2009).…”
Section: Discussioncontrasting
confidence: 56%
“…However, elevated levels of Pi increased the uptake rate of phosphorus (p , 0.05) (Fig. 4B), which is inconsistent with the report of Thiel (1988), who found that cyanobacteria showed higher rates of phosphate uptake under phosphate-limited conditions. Previous data had indicated that Cylindrospermopsis raciborskii was opportunistic with respect to Pi (Istvá novics et al 2000) and had rapid DIC uptake and storage capacity (Posselt et al 2009).…”
Section: Discussioncontrasting
confidence: 56%
“…We have previously studied arsenate toxicity in media with reduced amounts of phosphate (23) (a condition that does not affect the growth of any of the strains tested [ Fig. 3]), since this compound has a protective effect against arsenate toxicity, probably affecting arsenate transport (37,48) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the similarity in the uptake pattern between AsO 3À 4 and PO 3À 4 [17], arsenate could enter the cell of cyanobacteria through PST and PIT systems [20,27]. The PST system was slow and 100 times more specific for phosphate than arsenate, but the PIT system was fast and did not discriminate between phosphate and arsenate [20].…”
Section: Aeruginosamentioning
confidence: 99%